Catalytic self-activation of Ca-doped coconut shell for in-situ synthesis of hierarchical porous carbon supported CaO transesterification catalyst. (1st February 2021) - Sun, Hao; Sun, Kang; Wang, Fei; Liu, Yanyan; Ding, Linfei; Xu, Wei; Sun, Yunjuan; Jiang, Jianchun
Graphical abstract: Highlights: CaO/AC is synthesized by a one-step facile catalytic self-activation method. The hierarchical pore and ~15 nm CaO particles of catalyst are synchronously fabricated. A synergistic effect between mesopores and accessible base sites is revealed. Granular CaO/AC exhibits superior transesterification activity and recyclability. Abstract: This study reports a one-step facile synthesis of a novel heterogeneous granule base catalyst, dubbed CaO/AC that contains small calcium oxide (CaO) nanoparticles embedded within hierarchical activated carbon (AC). The CaO/AC hybrid exhibited a 98.59 wt% fatty acid methyl esters yield, with 89.75% less catalyst compared to pristine CaO. In addition, the CaO/AC granular catalyst, which was easily recovered without any post-treatment, presented sustainable catalytic activity after two cycles of transesterification. The calcium cations penetrated into the cell wall of coconut shell by vacuum impregnation, and the carbonization of cell wall suppressed the agglomeration of calcium compound, which was essential for the catalytic self-activation of Ca-doped coconut shell. The pyrolysis atmosphere and dwelling time were investigated to demonstrate the dual function of calcium. Owing to the catalytic effect of Ca during the self-activation process, the hierarchical activated carbon with improved mesopores was manufactured. On the other hand, CaO nanoparticles with an average size of 14.7 nm were in-situ encapsulated within the mesopores of hierarchical carbon matrices. The additional formation of mesopores and high dispersion of CaO nanoparticles were responsible for the enhanced inner mass transfer and the number of accessible alkaline sites in transesterification of triglycerides, leading to the high catalytic activity and stability of CaO/AC.